Analisis Pengaruh Variasi Media Pendingin Terhadap Sifat Mekanis Dan Struktur Mikro Sambungan Las Mig Gmaw Plat Baja SPHC-PO - Ramadhan, Umar; Sugeng, Margono (Peneliti.net, 2024)
Welding doesn't just heat up two specific metal parts to melt the base metal and filler metal until they allow it to re-solidify. In producing a complete weld by adding additional material or electrodes when heated so that they have the desired strength. This study uses the Quenching heat treatment process which is used as the main factor and aims to improve the mechanical properties of SPHC-PO low carbon steel in MIG welding results with SAE 10W-40 oil cooling medium, fan blower, and open air. The results showed that the highest tensile test was found in an open air cooling medium valued at 48.15 kgf/mm² compared to a fan blower cooling medium and SAE 10W-40 oil. The highest hardness value was found in the SAE 10W-40 oil cooling medium with a hardness value of 334.4 HV compared to the fan blower cooling medium and open air. The results of observing the micro structure of the pearlite phase were mostly found in the fan blower cooling medium 37% compared to the SAE 10W-40 oil cooling medium and open air.